2015
DOI: 10.1007/s40475-015-0036-0
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and Surveillance of Chikungunya

Abstract: Chikungunya virus (CHIKV), an arbovirus transmitted by Aedes mosquitoes, causes a disease characterised by fever, headache, skin rash, myalgias and severe arthralgias: the latter can persist for years. Following the first report in Africa in 1952, sporadic epidemics have been registered in Africa and in Asia before 2000. Since 2005, huge outbreaks have been reported, caused by globalisation (increasing displacement of humans and mosquitoes) and by an evolutionary success related to the adaptation of CHIKV to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 84 publications
(99 reference statements)
0
9
0
Order By: Relevance
“…Yet some studies for active surveillance have been conducted According to a study that investigated the cause of febrile illness in children during an inter-epidemic period in 5 Asian countries, CHIKV was responsible for 35% of all fevers [ 67 ]. Other seroprevalence studies in Africa confirmed that CHIKV was circulating endemically [ 66 ]. There was a program from the Pacific Public Health Surveillance Network for specific surveillance strategies of CHIKV, DENV and other febrile diseases including case detection and management, laboratory confirmation, vector control and raising awareness [ 68 ].…”
Section: Introduction Chikvmentioning
confidence: 92%
See 3 more Smart Citations
“…Yet some studies for active surveillance have been conducted According to a study that investigated the cause of febrile illness in children during an inter-epidemic period in 5 Asian countries, CHIKV was responsible for 35% of all fevers [ 67 ]. Other seroprevalence studies in Africa confirmed that CHIKV was circulating endemically [ 66 ]. There was a program from the Pacific Public Health Surveillance Network for specific surveillance strategies of CHIKV, DENV and other febrile diseases including case detection and management, laboratory confirmation, vector control and raising awareness [ 68 ].…”
Section: Introduction Chikvmentioning
confidence: 92%
“…If a disease is already endemic in a country, surveillance of this specific disease is only justified if appropriate actions to ban it are planned [ 66 ]. As there is no specific treatment for CHIKF available, the clinical outcome of a patient is only influenced by early detection when a more severe disease can be excluded.…”
Section: Introduction Chikvmentioning
confidence: 99%
See 2 more Smart Citations
“…About 3-25% of the patients are asymptomatic. 1 The hallmark symptoms of CHIKV include sudden onset of fever (typically 39-40°C) and severe arthralgia. 2 Other typical symptoms include headache, skin rash, retro-orbital pain, myalgia, neurological syndromes, insomnia, and myelopathy.…”
Section: Introductionmentioning
confidence: 99%